Comparison of Local Area Network Technologies: Ethernet (IEEE 802.3), ATM and WLAN/WiFi (IEEE 802.11g) (International Journal of Current Engineering and Technology, 2015)
A rigorous comparative study on Local Area Network technologies: Ethernet, ATM and WLAN with respect to the delay and throughput in each system is done in this work. These three technologies are prominent and used on a commercial scale in homes, campuses, offices, industries etc. However the data communication requirement and the working condition are not same in these places. The cost of these three technologies also is not the same. The paper compares the three technologies and can be helpful in selecting the LAN technology according to the requirements and place of deployment. The network simulator used in this work is OPNET 17.5 Academic Edition to calculate the delay and throughput of the three technologies under similar scenario conditions.
Keywords: Ethernet; ATM; WLAN